Growing Wasathiyah Islam: The Integration of Formal Education Curriculum and Islamic Boarding Schools. - Nugroho, Puspo; Az Zafi, Ashif; Aquil, Anzar (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This article aims to obtain information related to the integration model, the implementation of integration, and the process of strengthening the values of wasathiyah Islam based on the integration of the National and Local curriculum (Pesantren) at SMA Syubbanul Wathon located in Secang, Magelang, Central Java. Through a qualitative approach, Case study data were collected using observation techniques, documentation, and in-depth interviews with the principal, teachers, and several informants. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The research results show that the formal educational institution, SMA Syubbanul Wathon, is closely tied to the Pesantren API foundation as its principal manager; therefore, the integration Concept in place is an institutional integration between the School and the Pesantren within one area. Second, the process of integrating the School and Pesantren curricula in terms of learning is carried out through the Sift model, which involves dividing the day into morning and afternoon sessions. Third, the process of strengthening the values of Wasathiyah Islam is integrated between the two institutions, implemented through a multi-strategy approach that includes habituation, learning, and integrated religious studies within the school and pesantren/complex environment, covering various Aswaja study materials, the Yellow Book Aqidatul Awam, Minhajul Abidin, Fatkhul Qorib, Fathul Mu’in, Ta’limul Muta’alim, and several other classical Yellow Books.